1987
DOI: 10.1200/jco.1987.5.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of combined chemotherapy-radiotherapy approach in Hodgkin's disease: superiority of ABVD plus radiotherapy versus MOPP plus radiotherapy.

Abstract: In an attempt to reduce some of the delayed sequelae associated with combined modality therapy in Hodgkin's disease, we randomly tested stages IIB, IIIA, and IIIB MOPP (mechlorethamine, vincristine, procarbazine, and prednisone) v ABVD (Adriamycin, bleomycin, vinblastine, and dacarbazine). In 232 previously untreated patients, three cycles of either combination preceded and followed extensive irradiation. The complete remission rate was 80.7% following MOPP and 92.4% following ABVD (P less than .02). The 7-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
0
5

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(128 citation statements)
references
References 22 publications
3
119
0
5
Order By: Relevance
“…1-5 Despite optimal initial treatment, 20-50% of patients fail to enter remission or will relapse after achieving a complete response. [1][2][3][4][5][6][7] It has long been stated that patients who relapse after a first remission can be divided into two groups according to the length of their first remission. When patients relapse more than 1 year after the end of their first-line therapy, as many as 85% of them achieve a second complete remission when the same drug combination is used.…”
Section: Discussionmentioning
confidence: 99%
“…1-5 Despite optimal initial treatment, 20-50% of patients fail to enter remission or will relapse after achieving a complete response. [1][2][3][4][5][6][7] It has long been stated that patients who relapse after a first remission can be divided into two groups according to the length of their first remission. When patients relapse more than 1 year after the end of their first-line therapy, as many as 85% of them achieve a second complete remission when the same drug combination is used.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analyses have reported that combination therapy yields better relapse-free survival and overall survival than does chemotherapy alone (15,62,(70)(71)(72)(73). It is difficult to compare the results from chemotherapy alone with results from combination therapy since the composition of patient data varies from study to study.…”
Section: Advanced Disease: Stage Iiib-ivmentioning
confidence: 99%
“…In addition, RT (30)(31)(32)(33)(34)(35)(36) to residual nodal disease may be recommended in patients with a very good partial response after first-line chemotherapy with ABVD, Stanford V or BEACOPP regimens for advanced disease, and in patients with residual disease after salvage therapy with ASCT. In primary refractory disease, RT may have only a palliative role.…”
Section: The Role Of Radiotherapy For Limited Residual Diseasementioning
confidence: 99%
“…51 The 25-year updated results of MOPP regimens indicate a cure rate of about 50%. 52 After the introduction of the ABVD chemotherapy, a randomized study 33 demonstrated that MOPP+RT+MOPP was inferior to ABVD+RT+ABVD and two randomized studies 34,35 that MOPP alone was inferior in terms of failure free survival compared to the alternating use of MOPP and ABVD. The alternating MOPP and ABVD approach has therefore become the standard of therapy; randomized trials failed to demonstrate any difference between the alternating and the hybrid modality.…”
Section: First-line Therapy For Advanced Stage Diseasementioning
confidence: 99%
See 1 more Smart Citation